2014
DOI: 10.1021/jp507569e
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Antimalarial 2-Aryl-3H-indol-3-one Derivatives and Human Serum Albumin

Abstract: Binding of drugs to plasma proteins, such as albumin, is a major factor which determines their pharmacokinetics and pharmacological effects. Therefore, the interactions between human serum albumin (HSA) and four antimalarial compounds selected in the 2-aryl-3H-indol-3-one series have been investigated using UV-visible, fluorescence and circular dichroism (CD) spectroscopies. Compounds produced a static quenching of the intrinsic fluorescence of HSA. The thermodynamic parameters have shown that the binding reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…Probe experiments were carried out using warfarin and ibuprofen, which explicitly bound with sites I and II, respectively . The percentage of displacement by a probe can be calculated as follows : I=F/F0where F and F 0 are the fluorescence intensities of norgestrel–HSA in the absence and presence of probes, respectively. Figure D shows that the fluorescence intensity of the norgestrel–HSA system was obviously changed with the warfarin concentration increased and slightly changed with increasing ibuprofen concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Probe experiments were carried out using warfarin and ibuprofen, which explicitly bound with sites I and II, respectively . The percentage of displacement by a probe can be calculated as follows : I=F/F0where F and F 0 are the fluorescence intensities of norgestrel–HSA in the absence and presence of probes, respectively. Figure D shows that the fluorescence intensity of the norgestrel–HSA system was obviously changed with the warfarin concentration increased and slightly changed with increasing ibuprofen concentration.…”
Section: Resultsmentioning
confidence: 99%
“…K app d (Table 3) increased and PSH decreased for ANS-HSA after adding norgestrel, which indicated that ANS detached from HSA as norgestrel occupied some low-affinity binding sites of ANS [ 35,37]. On the other hand, the majority of bound ANS molecules existed in domain II because nearly all accessible hydrophobic residues of HSA were located there [31]. Therefore, the occupation of norgestrel to ANS implied that the binding site of norgestrel-HSA was site I, consistent with the molecular-modeling result.…”
Section: Determination the Surface Hydrophobicity Properties (Psh) Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…[19,27,30] The interaction studies between several antimalarial drugs and serum albumins have been published, based on fluorescence and other spectroscopic techniques. [31][32][33][34] Due to the presence of another transport protein (α 1 -acid glycoprotein) in the blood plasma, binding of antimalarial drugs to α 1 -acid glycoprotein has also been reported. [35] Emission of the protein fluorescence at 343 nm, when excited at 295 nm ( Figure 1A) can be assigned to the sole Trp residue (Trp-214) of HSA, located in the subdomain IIA of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant protein constituent of blood plasma, human serum albumin (HSA) can bind a wide range of endogenous and exogenous compounds and serves as an important carrier for a broad range of drugs (Ghuman et al, 2005;Zhu et al, 2015). This protein is composed of a single polypeptide chain, with three homologous α-helical domains I-III (Rakotoarivelo et al, 2014). Each domain contains two subdomains A and B, which correspond to two primary drugbinding sites, namely, sites I and II.…”
Section: Introductionmentioning
confidence: 99%